2011
DOI: 10.2459/jcm.0b013e3283403301
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation after typical atrial flutter ablation: a long-term follow-up

Abstract: Feasibility and clinical usefulness of high resolution sound map with cross plane method for AF ablation Yeong-Hwa CHUN (Eiwa Zen) (Japan) i1 OP 16-2 Robotic navigation for catheter ablation of atrial fibrillation-is there a learning curve? Fahd CHAHADI (Australia) i1 OP 16-3 Effect of atrial fibrillation on catheter-tissue contact during antral pulmonary vein isolation in humans: lower contact force at the left anterior pulmonary vein in atrial fibrillation compared to sinus or paced rhythm Saurabh KUMAR (Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
6
1
3
Order By: Relevance
“…We found, as in previous studies, that AF history was a strong predictor of AF occurrence after AFL ablation, with an almost 2‐fold increase in the risk of subsequent AF in patients with AF history prior to ablation. This finding is in contradiction with the hybrid therapy concept put forward in the late 1990s and early 2000s, in order to reduce the risk of AF recurrences .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found, as in previous studies, that AF history was a strong predictor of AF occurrence after AFL ablation, with an almost 2‐fold increase in the risk of subsequent AF in patients with AF history prior to ablation. This finding is in contradiction with the hybrid therapy concept put forward in the late 1990s and early 2000s, in order to reduce the risk of AF recurrences .…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in contradiction with the hybrid therapy concept put forward in the late 1990s and early 2000s, in order to reduce the risk of AF recurrences . However, several studies have shown that the risk of AF recurrence in patients with a history of AF was elevated, reaching as high as 70% at 3 years . Our results confirm the limited impact of hybrid therapy on the long‐term control of AF.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Ablacja cieśni trójdzielno-żylnej w przypadku trzepotania z prawego przedsionka zależnego od cieśni trójdzielno-żylnej (albo częste trzepotanie z krążeniem pobudzenia w kierunku przeciwnym do ruchu wskazówek zegara, albo rzadsze trzepotanie z krążeniem pobudzenia w kierunku zgodnym z ruchem wskazówek zegara) umożliwia przywrócenie i utrzymanie rytmu zatokowego w 90-95% przypadków [1002]. Takie leczenie może również ograniczyć występo-wanie nawrotów AF u wybranych pacjentów [1003,1004], a także ułatwić zapobieganie hospitalizacjom [1004,1005]. Ablacja cieśni trójdzielno-żylnej jest podobnie bezpieczna jak farmakoterapia antyarytmiczna, natomiast jest od niej bardziej skuteczna i zaleca się ją jako leczenie nawracającego trzepotania przedsionków [585][586][587]713].…”
Section: Postępowanie W Trzepotaniuunclassified
“…Ablation of the cavotricuspid isthmus for isthmus-dependent right atrial flutter (either the common counter-clockwise atrial flutter or the less-common clockwise atrial flutter) restores and maintains sinus rhythm with a success rate of 90-95%. 1002 It may also reduce AF recurrences in selected patients, 1003,1004 and help to prevent hospitalizations. 1004,1005 Isthmus ablation is comparably safe and more effective than antiarrhythmic drug therapy, and is recommended for recurrent atrial flutter.…”
Section: Management Of Atrial Fluttermentioning
confidence: 99%